In vitro free radical scavenging and antidiabetic activity of aqueous and ethanolic leaf extracts: a comparative evaluation of Argyreia pierreana and Matelea denticulata - Venkataiah Gudise; Bimalendu Chowdhury; Arehalli S. Manjappa (SpringerOpen, 2019)
Abstract Background Oxidation is believed to play a vital role in the pathogenesis of diabetes mellitus by lipid peroxidation; DNA and protein damage leads to the development of vascular complications like coronary heart disease, stroke, neuropathy, retinopathy, and nephropathy. The herbal preparations are complementary and alternative medicines to allopathic drugs which are believed to cause adverse events. Therefore, the current study was aimed to identify the novel plants, which belong to the genera Argyreia (Argyreia pierreana (AP)) and Matelea (Matelea denticulata (MD)), and assess the aqueous and ethanolic leaf extracts for in vitro antioxidant and antidiabetic potential by DPPH, OH•, superoxide, and glucose uptake and gene expression (GLUT-4 and PPARγ) studies using the L-6 cell line respectively. Results The preliminary scrutiny revealed the presence of polyphenols, flavonoids, terpenoids, steroids, tannins, alkaloids, and glycosides. The total phenolic and flavonoid contents of ethanolic extracts were found higher than those of aqueous extracts. The ethanolic extracts exhibited the superior antioxidant capacity when compared with aqueous extracts. However, the ethanolic extract of MD was shown superlative glucose uptake activity (72.54%) over control (0.037%) and GLUT-4 and PPARγ gene expressions (1.17 and 1.20) in term of folds respectively over cell control (1.00). Conclusion The ethanolic leaf extracts of both plants showed significant in vitro antioxidant and antidiabetic activities compare to aqueous extracts. The Matelea denticulata ethanolic leaf extract exhibited superior activity. This superior activity might be due to their higher phenolic and flavonoid content. However, further approaches are needed to define these activities.